Tinjauan Visual pada Iklan Pocari Sweat Bintang SMA - Wilda Rohim Hatta; Jupriani Jupriani (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Advertisements are an effective promotional medium to capture audience attention, especially through engaging visual approaches. One unique advertisement is Pocari Sweat Bintang SMA 2019, which employs 2D anime-style animation as a visual communication strategy. This study aims to analyze how the invitation element in the advertisement is visualized through storyline, scenes, and characters. Using Roland Barthes' semiotics analysis, this research explores the signs within the advertisement at both denotative and connotative levels. The findings reveal that Pocari Sweat effectively invites its audience through visuals that depict enthusiasm, freedom, and togetherness. By utilizing bright colors, movement symbolism, and character interactions, this advertisement successfully delivers a strong invitation message to participate in the Bintang SMA talent competition.